Saint Paul's epistle to the Ephesians the Greek text with notes and addenda - Westcott, Brooke Foss, 1825-1901 (Minneapolis, MN Klock and Klock Christian Publishers, 1967)
Includes bibliographical references, index and Greek text.
First published 1906.
Keywords: Bible. N.T. Ephesians -- commentaries